Crowdfunding and Fintech: business model sharia compliant - Biancone, Paolo Pietro; Secinaro, Silvana; Kamal, Mohamad (European Journal of Islamic Finance, 2019)
Focus on a concrete project, share the results, contain the risk. These are some of the precepts of Islamic finance. But they are also the cornerstones of crowdfunding. This is why this form of financing is cutting out its space. With an extra pillar: no interests. The resources are still limited, but the Muslim crowdfunding ecosystem is diversifying: from the most basic reward based on social lending, with an eye to the Fintech. FinTech refers to technofinance or financial technology, that is to say, the supply of services and financial products provided through the most modern technologies made available to ICT. The services provided by FinTech are essentially those of traditional finance: therefore, from simple transactions to payments, to brokering and risk management, typical and exclusive of this sector are the activities linked to electronic currencies such as for example, the Bitcoin.